A composite material, its preparation and use
Patent Information
- Application Number
- CN202310818393.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-05
AI Technical Summary
有机锂预锂化是将硅电极在有机锂溶液中浸泡一段时间,硅基负极可以有效地进行锂化,然而锂的用量很难精确控制,且需要额外的溶剂清洗的过程
采用先预锂预镁化和碳一步复合工艺,提升氧化亚硅负极的首次充放电效率和电子导电性。再通过氟化反应,将预锂预镁化硅氧复合负极包覆上一层金属氟化物快离子导体,进一步保证了氧化亚硅负极的稳定性以及极大的提升了材料的离子导电性能。
Smart Images

Figure CN116799182B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials, specifically to a composite material, its preparation method, and its application. Background Technology
[0002] With developed countries worldwide accelerating their efforts towards carbon neutrality, lithium-ion batteries, as the power system for new energy vehicles, have maintained a high-speed development trend in order to promote the construction of a clean, low-carbon, safe, and efficient energy system. In recent years, graphite-based carbon materials have been the mainstream anode material for power lithium-ion batteries, but they only have a capacity of 372 mAh / g. -1 The theoretical specific capacity is limited, and lithium dendrites are easily formed during charging and discharging, posing serious safety hazards. Therefore, the development of commercial anode materials with higher specific capacity and higher safety has become an urgent market demand.
[0003] Silicon suboxide anodes are used in power batteries. During the initial charging process, due to the Li... + Alloying with silicon is accompanied by the formation of a solid electrolyte interphase (SEI) film and the generation of inactive Li₂O, leading to significant lithium loss and a substantial reduction in the material's initial coulombic efficiency. With increasing silicon doping levels, the irreversible lithium loss during the first cycle further reduces the overall cell's energy density, severely hindering the commercial application of high-silicon-content anode materials. To address this issue, pre-lithiation to provide additional active lithium to the battery has been widely accepted as one of the most promising strategies. Pre-lithiation refers to pre-storing a certain amount of lithium in high-capacity anode materials to compensate for the irreversible lithium capacity loss during the first cycle, including both positive and negative electrode pre-lithiation. Pre-lithiation of anode materials involves intercalating lithium into the anode material to form a lithiated material and the initial SEI film. For example, pre-lithiation of silicon suboxide involves reacting to generate a composite product of lithium silicate, silicon, and lithium oxide as the electrode material.
[0004] Researchers have developed various pre-lithiation methods, including lithium metal particle doping pre-lithiation, lithium foil addition pre-lithiation, membrane-free self-discharge pre-lithiation, battery electrochemical pre-lithiation, molten thermal lithiation, and organolithium pre-lithiation. Among these, lithium metal particle doping pre-lithiation (SLMP) involves encapsulating a lithium core with an inert lithium carbonate shell to prepare inert lithium powder, which is then added to a silicon-carbon anode slurry to form an electrode. However, SLMP is incompatible with common solvents, leading to incompatibility between the anode material and the binder, affecting the coating effect of the electrode and limiting its industrial application. Lithium foil addition pre-lithiation involves directly pressing lithium foil onto the anode to form a hybrid electrode, where the lithium foil acts as a lithium source to compensate for irreversible lithium loss during the first cycle. Since pure lithium metal cannot exist stably in a dry air atmosphere, it poses significant challenges to large-scale manufacturing. Self-discharge pre-lithiation in membrane-free batteries involves bringing a prepared electrode into close contact with a lithium foil in an electrolyte solution. A short circuit is then applied to induce oxidation and corrosion on one side of the lithium foil, a process similar to electrolyte reduction and SEI formation. However, this method struggles to precisely control the degree of pre-lithiation. Electrochemical pre-lithiation allows for precise control of current and cutoff voltage, making it easier to control the degree and rate of pre-lithiation. However, it requires additional temporary battery assembly, making the process cumbersome and limiting its industrial application. Molten thermal lithiation of lithium alloy compounds typically involves high chemical reactivity, making them unstable in air and incompatible with current slurry-coating-based electrode fabrication processes. Organolithium pre-lithiation involves immersing a silicon electrode in an organic lithium solution for a period of time, allowing for effective lithiation of the silicon-based anode. However, precise control of the lithium dosage is difficult, and an additional solvent cleaning process is required. Summary of the Invention
[0005] The purpose of this invention is to address at least one of the aforementioned deficiencies in the prior art. For example, one objective of this invention is to provide a method for preparing a composite material that improves the initial charge-discharge efficiency and electronic conductivity of a silicon suboxide anode.
[0006] To achieve the above objectives, one aspect of the present invention provides a method for preparing a composite material, the method comprising: uniformly mixing a silicon-oxygen anode, a lithium source, a magnesium source, and an organic solid carbon source to obtain a first precursor; calcining the first precursor under vacuum conditions to obtain a second precursor, wherein the vacuum calcination temperature is 600℃~1000℃; dispersing the second precursor in an acid washing solution for acid washing, followed by washing, filtration, and drying to obtain a third precursor; heating the third precursor, a metal salt solution, and a fluoride in a solvent in a water bath until the solvent evaporates completely to obtain a fourth precursor; and calcining the fourth precursor under an inert atmosphere to obtain the composite material.
[0007] In an exemplary embodiment, the silicon-oxygen anode may be silicon suboxide (SiO2). x0 < x < 2; the lithium source may include one or more of lithium carbonate, lithium hydroxide, lithium nitride, lithium hydride, lithium oxide, lithium amide, methyl lithium, and hexyl lithium; the magnesium source may include one or more of magnesium carbonate, magnesium oxide, magnesium hydroxide, and metallic magnesium powder; the organic solid carbon source may include one or more of glucose, sucrose, terephthalic acid, polyvinyl alcohol, polyacrylate, and carboxymethyl cellulose; by mass percentage, the silicon suboxide content is 1% to 90%, the lithium source is 1% to 50%, and the magnesium source is 1% to 50%.
[0008] In an exemplary embodiment, the calcination temperature can be 400℃~1000℃, and the calcination time can be 1h~10h; the pickling solution can include one or more of phosphoric acid, hydrochloric acid, acetic acid, citric acid, formic acid, hypochlorous acid, and boric acid; the concentration of the pickling solution can be 0.1M~5M, and the pickling time can be 1min~300min.
[0009] In an exemplary embodiment, the metal salt may be one or more of magnesium sulfate, magnesium nitrate, magnesium carbonate, magnesium chloride, magnesium hydroxide, aluminum sulfate, aluminum nitrate, aluminum chloride, calcium sulfate, and calcium chloride; the fluoride may be one of ammonium fluoride, ammonium hydrogen fluoride, and hydrogen fluoride; the solvent may be one or more of water, ethanol, methanol, and acetone; by mass percentage, the third precursor may be 1% to 90%, the metal salt may be 1% to 50%, the ammonium fluoride may be 1% to 50%, and the temperature of the water bath stirring may be 30°C to 90°C.
[0010] In an exemplary embodiment, the composite material may contain 1% to 99% silicon, 0.1% to 90% carbon, 0.1% to 20% lithium, and 0.1% to 10% metal fluoride by mass percentage.
[0011] Another aspect of the present invention provides a composite material obtained by the preparation method described above, the composite material having a core-shell structure comprising a core of lithium magnesium silicate / carbon and a shell of metal fluoride fast ion conductor.
[0012] In an exemplary embodiment, the thickness of the core can be 500~3000nm, and the thickness of the outer shell can be 10~1000nm.
[0013] Another aspect of the present invention provides the application of the composite material described above as a negative electrode active material for batteries.
[0014] Another aspect of the present invention provides a negative electrode active material, wherein the negative electrode active material may be Li x Mg y Siz O n / C@MgF2, the negative electrode active material is based on Li x Mg y Si z O n It has a core-shell structure with MgF2 as the core and MgF2 as the shell.
[0015] Another aspect of the present invention provides a negative electrode comprising: a current collector; and a negative electrode material layer located on the current collector, wherein the negative electrode material layer comprises the negative electrode active material as described above.
[0016] In another aspect of the present invention, a lithium secondary battery is provided, the lithium secondary battery comprising: a positive electrode; a negative electrode as described above; and an electrolyte located between the positive electrode and the negative electrode.
[0017] Compared with the prior art, the beneficial effects of the present invention include the following: A pre-lithiation and pre-magnesiumization followed by a one-step carbon composite process is employed to improve the initial charge-discharge efficiency and electronic conductivity of the silicon suboxide anode. Then, a fluorination reaction is used to coat the pre-lithiation and pre-magnesiumization silicon-oxygen composite anode with a layer of metal fluoride fast ion conductor, further ensuring the stability of the silicon suboxide anode and significantly improving the material's ionic conductivity. Attached Figure Description
[0018] The above and other objects and / or features of the present invention will become clearer from the following description taken in conjunction with the accompanying drawings, in which: Figure 1 An X-ray diffraction pattern of the composite material obtained by Example 1 of the present invention is shown.
[0019] Figure 2 The following is a surface scan of the composite material obtained by Example 1 of the present invention.
[0020] Figure 3 A scanning electron microscope image of the composite material obtained in Example 1 of the present invention is shown.
[0021] Figure 4 The diagram shows the test results of the button cell obtained by Example 1 of the present invention. Detailed Implementation
[0022] The composite materials of the present invention, their preparation methods, and applications will be described in detail below with reference to exemplary embodiments.
[0023] In this document, the terms “or” and “and / or” include any and all combinations of one or more of the associated listed items. Throughout the disclosure, the expression “at least one of a, b, and c” means only a, only b, only c, both a and b, both a and c, both b and c, all of a, b, and c, or variations thereof.
[0024] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the inventive concept. As used herein, unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” are also intended to include the plural forms. It will also be understood that when the terms “comprising” and / or “including” and variations thereof are used in this specification, they indicate the presence of the stated features, integrals, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, integrals, steps, operations, elements, components, and / or groups thereof. Depending on the context, the symbol “ / ” as used herein may be interpreted as meaning “and” or “or.”
[0025] Although the terms “first,” “second,” etc., may be used herein to describe various elements, components, regions, and / or layers, these elements, components, regions, and / or layers should not be limited by these terms. These terms are used only to distinguish one component from another and are not for limiting purposes. Some components may be omitted in the accompanying drawings. However, omissions are intended to aid understanding of the disclosure and not to exclude the omitted components.
[0026] The applicant discovered that pre-lithiation of silicon suboxide and surface coating with a carbon layer can improve the initial efficiency, rate capability, and stability of silicon suboxide anodes. However, using only a single-layer or double-layer coating structure to improve the interfacial stability and electrochemical performance of the silicon suboxide anode often only addresses one aspect of the material during modification. Using single-layer carbon coating or single-layer fluoride coating in the process can only improve the performance of pre-lithiated silicon suboxide from the perspective of either electronic conductivity or lithium-ion conductivity. It is generally believed that double coating with fluoride and carbon may result in different polarities at the interface of the coating materials, making it difficult to achieve a uniform coating structure during synthesis.
[0027] According to one aspect of the present invention, a process technology is provided for fluoride-modified coating of pre-lithiated pre-magnesium silicon-oxygen composite anode material. The pre-lithiated pre-magnesium and carbon composites are completed in one step to form a composite material of pre-lithiated pre-magnesium silicon-oxygen and carbon, which improves the first charge-discharge efficiency of silicon suboxide anode and improves the electronic conductivity of pre-lithiated pre-magnesium anode material. Furthermore, a fast ion conductor metal fluoride is uniformly coated on the surface of the pre-lithiated pre-magnesium silicon-oxygen / carbon composite anode to improve the ionic conductivity of silicon-oxygen anode and improve the stability of the interface in slurry mixing.
[0028] In an exemplary embodiment, a method for preparing a composite material is provided, the method comprising: S1. The silicon-oxygen anode, lithium source, magnesium source and organic solid carbon source are mixed evenly to obtain the first precursor.
[0029] Specifically, a certain amount of silicon-oxygen anode material, lithium source, magnesium source, and organic solid carbon source can be weighed and thoroughly stirred together in a vacuum planetary stirrer until homogeneous to form the first precursor. The mixing time can be from 30 min to 600 min.
[0030] Optionally, the silicon-oxygen anode can be silicon suboxide (SiO2). x (0 < x < 2), for example, it could be silicon monoxide.
[0031] The lithium source may include one or more of lithium carbonate, lithium hydroxide, lithium nitride, lithium hydride, lithium oxide, lithium aminoide, lithium methyl and hexyl lithium.
[0032] Metal precursors may include one or more of magnesium carbonate, magnesium oxide, magnesium hydroxide, and magnesium powder.
[0033] Organic solid carbon sources may include one or more of glucose, sucrose, terephthalic acid, polyvinyl alcohol, polyacrylate, and carboxymethyl cellulose.
[0034] By mass percentage, the silicon suboxide content can be 1% to 90%, the lithium source can be 1% to 50%, and the magnesium source can be 1% to 50%.
[0035] S2. The first precursor is calcined under vacuum conditions to obtain the second precursor, wherein the vacuum calcination temperature is 600℃~1000℃.
[0036] The first precursor obtained from S1 was heated to the target calcination temperature in a tube furnace under vacuum at a rate of 1℃ / min to 10℃ / min, and held at that temperature for 4 hours before being naturally cooled to obtain the second precursor.
[0037] The target calcination temperature can be between 600℃ and 1000℃, such as 600℃, 800℃, and 1000℃. Temperatures below 600℃ will prevent the pre-lithiation and pre-magnesification temperature from being reached, while temperatures above 1000℃ will cause the pre-lithiated lithium magnesium silicate to decompose into silicon oxide, lithium oxide, and magnesium oxide, thus failing to achieve the desired effect. The calcination time (i.e., the holding time mentioned earlier) can be between 1 hour and 10 hours, such as 1 hour, 5 hours, and 7 hours. Choosing an appropriate holding time ensures that the silicon suboxide precursor can be pre-lithiated and pre-magnesified more thoroughly; if the time is too short, most of the product may only be silicon suboxide or lithium silicate.
[0038] In this embodiment, the heating rate can be 5°C / min.
[0039] S3. Disperse the second precursor in an acid washing solution and acid wash, then wash, filter and dry to obtain the third precursor.
[0040] Specifically, a certain amount of the second precursor can be weighed and dissolved in a certain proportion of acidic solution for acid treatment. The sample is then washed and filtered until the sample surface is neutral, and then the sample is dried to obtain the third precursor.
[0041] The pickling solution may include one or more of phosphoric acid, hydrochloric acid, acetic acid, citric acid, formic acid, hypochlorous acid, and boric acid. The concentration of the pickling solution may be 0.1M to 5M, for example, 0.5M or 1M. The pickling time may be 1 min to 300 min.
[0042] S4. Heat the third precursor, metal salt solution and fluoride in a water bath in a solvent until the solvent evaporates completely to obtain the fourth precursor.
[0043] Specifically, a certain amount of the dried third precursor in S3 is mixed with a metal salt solution and fluoride in a solvent, heated and stirred in a water bath, and evaporated to dryness to obtain the fourth precursor.
[0044] The metal salt can be one or more of the following: magnesium sulfate, magnesium nitrate, magnesium carbonate, magnesium chloride, magnesium hydroxide, aluminum sulfate, aluminum nitrate, aluminum chloride, calcium sulfate, and calcium chloride.
[0045] Fluorides can be one of ammonium fluoride, ammonium hydrogen fluoride, and hydrogen fluoride.
[0046] The solvent can be one or more of water, ethanol, methanol, and acetone, such as ethanol.
[0047] By mass percentage, the third precursor can be 1% to 90%, the metal salt can be 1% to 50%, the ammonium fluoride can be 1% to 50%, and the water bath stirring temperature can be 30℃ to 90℃.
[0048] In other words, Li in S4 x Mg y Si z O n The mass ratio of C is 1%~90%, the mass ratio of metal salt is 1%~50%, and the mass ratio of fluoride is 1%~50%.
[0049] S5. The fourth precursor is calcined in an inert atmosphere to obtain the composite material.
[0050] Specifically, the fourth precursor obtained in S4 is calcined at a certain high temperature and protected by an inert gas to obtain a fluoride-modified pre-lithium pre-magnesium silicon-oxygen anode composite material.
[0051] The inert gas in S5 is one or more of nitrogen, argon, and helium. The calcination temperature is 400℃~1000℃, for example 600℃, 800℃, or 1000℃. The calcination time is 1h~10h, for example 1h, 5h, or 7h.
[0052] The prepared composite material can contain 1% to 99% silicon, 0.1% to 90% carbon, 0.1% to 20% lithium, and 0.1% to 10% metal fluoride by mass percentage.
[0053] The chemical formula of the composite material prepared in the exemplary embodiment of the present invention is Li. x Mg y Si z O n / C@MgF2. In this invention, the expression "@" is conventional in the art. Specifically, "@" generally refers to a core-shell structure, such as Li in this invention. x Mg y Si z O n / C@MgF2 refers to Li x Mg y Si z O n It has a core-shell structure with MgF2 as the core and MgF2 as the shell.
[0054] The fluoride-modified pre-lithiated silicon oxide composite material prepared in the exemplary embodiment of the present invention has a core-shell structure, including a core of lithium magnesium silicate / carbon and a shell of metal fluoride fast ion conductor.
[0055] The core has a thickness of 500–3000 nm, and the outer shell has a thickness of 10–1000 nm. The median particle size of the fluoride-modified pre-lithium pre-magnesium silicate composite material is 0.5–30 μm.
[0056] According to an exemplary embodiment of the present invention, a one-step pre-lithiation and carbon composite process is employed to improve the initial charge-discharge efficiency and electronic conductivity of the silicon suboxide anode. This application first forms a composite structure with carbon interpenetrating within the pre-lithiation and pre-magnesium-coated silicon suboxide through a one-step pre-lithiation and pre-magnesium-coated process. This composite structure differs from traditional coating structures; carbon is not used as a coating layer but rather as an interpenetrating carbon structure, enhancing the conductivity of the silicon suboxide material on a three-dimensional scale. Then, further fluoride coating is applied to modify the surface, thus avoiding the problem of different polarities at the interface between the fluoride and carbon layers, which makes it difficult to achieve a uniform coating structure during synthesis. Finally, a fluorination reaction coats the pre-lithiation and pre-magnesium-coated silicon-oxygen composite anode with a layer of metal fluoride fast ion conductor, further ensuring the stability of the silicon suboxide anode and significantly improving the material's ionic conductivity.
[0057] According to another aspect of the present invention, a composite material having the chemical formula Li is provided. x Mg y Si z O n / C@MgF 2。 The composite material has a core-shell structure, consisting of a core of lithium magnesium silicate / carbon and a shell of metal fluoride fast ion conductors.
[0058] Among them, the fluoride-modified pre-lithium pre-magnesium silicate composite material Li x Mg y Si z O n / C@MgF2 can be prepared by the composite material preparation method described in the exemplary embodiments above.
[0059] According to another aspect of the present invention, an application of the composite material as described above as a negative electrode active material for a battery is provided, wherein the chemical formula of the composite material is Li. x Mg y Si z O n / C@MgF 2。 The composite material has a core-shell structure, consisting of a core of lithium magnesium silicate / carbon and a shell of fast-ion conductor metal fluoride. The composite material is Li... x Mg y Si z O n / C@MgF2 can be prepared by the composite material preparation method described in the exemplary embodiments above.
[0060] According to another aspect of the present invention, a negative electrode active material is provided, wherein the negative electrode active material is Li x Mg y Si zO n / C@MgF 2, Among them, the negative electrode active material is Li x Mg y Si z O n It has a core-shell structure with MgF2 as the core and MgF2 as the shell.
[0061] composite material Li x Mg y Si z O n / C@MgF2 can be prepared by the composite material preparation method described in the exemplary embodiments above.
[0062] According to another aspect of the present invention, a negative electrode is provided, characterized in that the negative electrode comprises: a current collector; and a negative electrode material layer located on the current collector, wherein the negative electrode material layer may comprise a negative electrode active material according to any of the above embodiments. That is, the negative electrode material layer may comprise a negative electrode active material, which may be a composite material Li. x Mg y Si z O n / C@MgF 2, It refers to Li x Mg y Si z O n It has a core-shell structure with MgF2 as the core and MgF2 as the shell.
[0063] Among them, the composite material Li x Mg y Si z O n / C@MgF2 can be prepared by the composite material preparation method described in the exemplary embodiments above.
[0064] In this embodiment, the negative electrode material layer may further include a conductive material and a binder, wherein the mass ratio of the negative electrode active material, the conductive agent, and the binder is 60-80:20-10:20-10. That is, the negative electrode material layer may include approximately 60 to 80 parts by mass of the negative electrode active material, approximately 20 to 10 parts by mass of the conductive agent, and approximately 20 to 10 parts by mass of the binder.
[0065] Here, the binder, which facilitates the bonding between the lithium transition metal oxide (i.e., the positive electrode active material or inorganic material) and the conductive material, and also facilitates the bonding to the current collector, may be included between the positive electrode current collector and the positive electrode active material layer, within the positive electrode active material layer, between the positive electrode active material layer and the organic layer, or within the inorganic layer. For example, the binder may be at least one selected from polyvinylidene fluoride, polyacrylonitrile, carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). For example, when two or more binders as described above are present, various copolymers polymerized with two or more binders may be used.
[0066] Here, the conductive material further improves conductivity by providing a conductive path to the aforementioned positive electrode active material or inorganic material. As the conductive material, any material commonly used in lithium secondary batteries can be used, and examples include carbon-based materials such as carbon black, acetylene black, Ketjen black, and carbon fibers (e.g., vapor-grown carbon fibers); the content of the conductive material can be appropriately adjusted and used. Meanwhile, the negative electrode can be manufactured by, for example, mixing the negative electrode active material, conductive material, binder, and solvent to prepare a negative electrode active material composition. The negative electrode plate can be manufactured by directly coating and drying the negative electrode active material composition onto a metal current collector.
[0067] According to another aspect of the present invention, a lithium secondary battery is provided, comprising: a positive electrode; a negative electrode as described above; and an electrolyte located between the positive electrode and the negative electrode.
[0068] In this implementation, the lithium secondary battery can be used in electric bicycles or power tools.
[0069] Lithium-ion batteries can be used not only as power sources for small devices, but also as unit cells in battery modules for medium / large devices that include multiple batteries.
[0070] Examples of medium / large-sized installations may include, but are not limited to: xEVs, including power tools, electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles, including electric bicycles and electric scooters; electric golf carts; electric trucks; electric commercial vehicles; and energy storage systems. Lithium-ion batteries can be used in all other applications requiring high output, high voltage, and high-temperature operation.
[0071] The exemplary embodiments of the present invention described above will be further explained and illustrated below with reference to specific examples.
[0072] Example 1 (1) First, weigh 10g of silicon suboxide, 1g of lithium carbonate, 0.1g of magnesium oxide and 0.5g of sucrose. Add the weighed powder to a planetary stirrer and vacuum it. Then stir until the powder is evenly dispersed.
[0073] (2) The precursor obtained above was heated to 600°C in a tube furnace under vacuum at a rate of 5°C / min, held at that temperature for 4 hours, and then naturally cooled to obtain Li. x Mg y Si z O n / C composite material, where the active material is a composite product of lithium Li2MgSiO4, Si and Li2SiO3, that is, a mixed product, so its xyzn value cannot be determined.
[0074] (3) The Li obtained above x Mg y Si z O n Take 1g of the / C composite material and dissolve it in 50ml of 0.1M hydrochloric acid solution for acid treatment. Then wash and filter the sample until the sample surface is neutral, and then dry the sample.
[0075] (4) Dissolve 1g of the above-obtained composite material in 50ml of deionized water, add 0.01g of magnesium nitrate, and then slowly add 10ml of 0.1M ammonium fluoride solution. Stir in a water bath at 60℃ until the solvent evaporates completely to obtain a powder sample.
[0076] (5) The sample obtained above was heated to 400°C at a rate of 5°C / min in a tube furnace under an inert atmosphere, held at that temperature for 4 hours, and then naturally cooled to obtain Li. x Mg y Si z O n / C@MgF2 composite material.
[0077] Figure 1 The X-ray diffraction pattern of the composite material obtained in this example confirms the successful synthesis of the pre-lithium pre-magnesium silicon-oxygen anode. Figure 2 The elemental surface scan of the composite material obtained in this example shows that magnesium and fluorine are uniformly distributed on the material surface, indicating successful coating with metal fluoride salts. Figure 3 The scanning electron microscope image obtained for this example shows that a clear coating product was formed on the surface of the pre-lithium pre-magnesium silicon oxide anode.
[0078] (Li) x Mg y Si z O n (Performance testing of / C@MgF2 composite material as a negative electrode material and in the assembly of lithium batteries) For Li x Mg y Si z O n The / C@MgF2 composite material was subjected to constant current charge-discharge testing, and the active material (i.e., the prepared Li) was used. x Mg y Si z O n The composite material (C@MgF2) was mixed with CMC and acetylene black in an 8:1:1 ratio to form a slurry, which was then coated onto copper foil. After drying the electrode, it was made into a disc with a diameter of 1.4 cm. Lithium metal was used as the counter electrode. 1 M LiPF6 was dissolved in EC:DEC:DMC in a volume ratio of 1:1:1 and 5% FEC was added as the electrolyte. The electrode was assembled into an R2032 coin cell for testing. The test current density was 1 A / g.
[0079] Test results are as follows Figure 4 As shown, the initial discharge specific capacity is 1388 mAh / g, the initial charge specific capacity is 1246 mAh / g, and the reversible specific capacity after 50 cycles is 532 mAh / g. The gas production test conditions were as follows: 2g of sample was added to 4g of a 5wt% sodium hydroxide solution, and the mixture was allowed to stand at 45℃ for 48 hours, during which the gas production volume was recorded.
[0080] Example 2 Following the method in Example 1, the difference is that the lithium source in step (1) is changed to lithium hydroxide, the magnesium source is changed to magnesium hydroxide, and the organic solid carbon source is changed to polyacrylonitrile. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@MgF2 composite material. The metal fluoride accounts for 1 wt% of the silicon-based anode material.
[0081] Example 3 Following the method in Example 1, the difference is that the metal salt in step (4) is replaced with 0.01g of aluminum nitrate, and the fluoride is replaced with hydrogen fluoride. The other steps are the same as in Example 1, yielding Li. x Mg y Si z O n / C@AlF3 composite material. The metal fluoride comprises 1 wt% of the silicon-based anode material.
[0082] Example 4 Following the method in Example 1, the difference is that the magnesium source in step (1) is replaced with magnesium oxide, and the metal salt solution in step (4) is replaced with 0.01g aluminum nitrate. The other steps are the same as in Example 1, yielding Li. x Mg y Siz O n / C@AlF3 composite material. The metal fluoride comprises 1 wt% of the silicon-based anode material.
[0083] Example 5 Following the method in Example 1, the difference is that the magnesium source in step (1) is replaced with magnesium powder, and the metal salt solution in step (4) is replaced with 0.01g of calcium chloride. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 1 wt% of the silicon-based anode material.
[0084] Example 6 Following the method in Example 1, the difference is that the metal salt in step (4) is replaced with 0.02g of magnesium nitrate, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@MgF2 composite material. Metal fluorides account for 2 wt% of the silicon-based anode material.
[0085] Example 7 Following the method in Example 1, the difference is that the metal salt in step (4) is replaced with 0.05g of magnesium nitrate, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@MgF2 composite material. Metal fluorides comprise 5 wt% of the silicon-based anode material.
[0086] Example 8 The method is the same as in Example 1, except that the metal salt in step (1) is replaced with 0.1g of magnesium nitrate. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@MgF2 composite material. Metal fluorides comprise 10 wt% of the silicon-based anode material.
[0087] Example 9 The method is the same as in Example 1, except that the magnesium source in step (1) is replaced with magnesium carbonate, and the holding temperature in step (2) is 800℃. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@MgF2 composite material. The metal fluoride accounts for 1 wt% of the silicon-based anode material.
[0088] Example 10 The method is the same as in Example 1, except that the magnesium source in step (1) is replaced with magnesium powder, and the holding temperature in step (2) is 900℃. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@MgF2 composite material. The metal fluoride accounts for 1 wt% of the silicon-based anode material.
[0089] Example 11 Following the method in Example 3, the difference is that the metal salt in step (4) is replaced with 0.02g of aluminum nitrate, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@AlF3 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0090] Example 12 Following the method in Example 9, the difference is that the heat preservation temperature in step (2) is 700℃, and the other steps are the same as in Example 1, to obtain Li. x Mg y Si z O n / C@AlF3 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0091] Example 13 Following the method in Example 9, the difference is that the heat preservation temperature in step (2) is 900℃, and the other steps are the same as in Example 1, to obtain Li. x Mg y Si z O n / C@AlF3 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0092] Example 14 Following the method in Example 3, the difference is that the metal salt in step (4) is replaced with 0.05g of aluminum nitrate, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@AlF3 composite material. Metal fluorides comprise 5 wt% of the silicon-based anode material.
[0093] Example 15 Following the method in Example 3, the difference is that the metal salt in step (4) is replaced with 0.1g of aluminum nitrate, while the other steps are the same as in Example 1, to obtain Li x Mgy Si z O n / C@AlF3 composite material. Metal fluorides comprise 10 wt% of the silicon-based anode material.
[0094] Example 16 Following the method in Example 5, the difference is that the metal salt in step (4) is replaced with 0.02g of calcium chloride, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0095] Example 17 Following the method in Example 5, the difference is that the holding temperature in step (2) is 700℃, and the metal salt solution in step (4) is replaced with 0.02g of calcium chloride. The other steps are the same as in Example 1, yielding Li. x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0096] Example 18 Following the method in Example 5, the difference is that the holding temperature in step (2) is 900℃, and the metal salt solution in step (4) is replaced with 0.02g of calcium chloride. The other steps are the same as in Example 1, yielding Li. x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0097] Example 19 Following the method in Example 5, the difference is that the metal salt in step (4) is replaced with 0.05g of calcium chloride, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 5 wt% of the silicon-based anode material.
[0098] Example 20 Following the method in Example 5, the difference is that the metal salt in step (4) is replaced with 0.1g of calcium chloride, while the other steps are the same as in Example 1, to obtain Li x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 10 wt% of the silicon-based anode material.
[0099] Example 21 The method is the same as in Example 1, except that the holding temperature in step (5) is 600℃, and the metal salt in step (4) is replaced with 0.1g of magnesium sulfate. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@MgF2 composite material. Metal fluorides comprise 10 wt% of the silicon-based anode material.
[0100] Example 22 The method is the same as in Example 1, except that the holding temperature in step (5) is 800℃, and the metal salt solution in step (4) is replaced with 0.1g of magnesium chloride. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@MgF2 composite material. Metal fluorides comprise 10 wt% of the silicon-based anode material.
[0101] Example 23 The method is the same as in Example 1, except that the holding temperature in step (5) is 700℃, and the metal salt solution in step (4) is replaced with 0.02g of calcium chloride. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0102] Example 24 The method is the same as in Example 1, except that the holding temperature in step (5) is 800℃, and the metal salt in step (4) is replaced with 0.02g of calcium sulfate. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@CaF2 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0103] Example 25 The method is the same as in Example 1, except that the holding temperature in step (5) is 900℃, and the metal salt solution in step (4) is replaced with 0.02g of aluminum nitrate. The other steps are the same as in Example 1, and Li is obtained. x Mg y Si z O n / C@AlF3 composite material. Metal fluorides comprise 2 wt% of the silicon-based anode material.
[0104] Table 1 shows the electrochemical performance of the fluoride-modified pre-lithiated silicon-oxygen composite materials obtained in the above examples. It can be seen that the composite materials can all obtain excellent electrochemical performance, indicating that pre-lithiation in the composite materials improves the first charge and discharge efficiency by accelerating ion transport through fast ion conductors and carbon layer coating, thereby improving the rate performance of the negative electrode.
[0105] Table 1 Electrochemical properties of fluoride-modified pre-lithiated composite materials
[0106] In summary, this invention provides a fluoride-modified pre-lithiated pre-magnesium silicate composite anode material preparation technology. It employs a one-step pre-lithiation and carbon composite process to improve the initial charge-discharge efficiency and electronic conductivity of the silicon suboxide anode. Furthermore, through a fluorination reaction, a layer of metal fluoride fast ion conductor is coated onto the pre-lithiated pre-magnesium silicate composite anode, further ensuring the stability of the silicon suboxide anode and significantly enhancing the material's ionic conductivity.
[0107] Although the invention has been described above in conjunction with exemplary embodiments, those skilled in the art will understand that various modifications and changes can be made to the exemplary embodiments of the invention without departing from the spirit and scope defined by the claims.
Claims
1. A method for preparing a composite material, characterized in that, The preparation method includes: The silicon-oxygen anode, lithium source, magnesium source and organic solid carbon source are mixed evenly to obtain the first precursor; The first precursor is calcined under vacuum conditions to obtain the second precursor, wherein the vacuum calcination temperature is 600℃~1000℃; The second precursor was dispersed in an acid washing solution and then washed, filtered, and dried to obtain the third precursor. The third precursor, metal salt solution, and fluoride were heated in a water bath in a solvent until the solvent evaporated completely, yielding the fourth precursor; and The fourth precursor was calcined in an inert atmosphere to obtain the composite material. The calcination temperature is 400℃~1000℃, and the calcination time is 1h~10h; The pickling solution includes one or more of phosphoric acid, hydrochloric acid, acetic acid, citric acid, formic acid, hypochlorous acid, and boric acid; The concentration of the pickling solution is 0.1M to 5M, and the pickling time is 1min to 300min.
2. The method for preparing the composite material according to claim 1, characterized in that, The silicon-oxygen anode is silicon suboxide (SiO₂). x , 0 < x < 2; The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium nitride, lithium hydride, lithium oxide, lithium aminoide, lithium methyl, and hexyl lithium. The magnesium source includes one or more of magnesium carbonate, magnesium oxide, magnesium hydroxide, and metallic magnesium powder; The organic solid carbon source includes one or more of glucose, sucrose, terephthalic acid, polyvinyl alcohol, polyacrylate, and carboxymethyl cellulose; The silicon suboxide content is 1% to 90% by mass percentage, the lithium source is 1% to 50%, and the magnesium source is 1% to 50%.
3. The method for preparing the composite material according to claim 1, characterized in that, The metal salt is one or more of magnesium sulfate, magnesium nitrate, magnesium carbonate, magnesium chloride, magnesium hydroxide, aluminum sulfate, aluminum nitrate, aluminum chloride, calcium sulfate, and calcium chloride. The fluoride is one of ammonium fluoride, ammonium bifluoride, and hydrogen fluoride; The solvent is one or more of water, ethanol, methanol and acetone; The third precursor comprises 1% to 90% by mass percentage, the metal salt comprises 1% to 50%, the ammonium fluoride comprises 1% to 50%, and the temperature of the water bath stirring is 30°C to 90°C.
4. The method for preparing the composite material according to claim 1, characterized in that, The composite material contains 1% to 99% silicon, 0.1% to 90% carbon, 0.1% to 20% lithium, and 0.1% to 10% metal fluoride by mass percentage.
5. A composite material, characterized in that, The composite material is obtained by the preparation method according to any one of claims 1 to 4, and the composite material has a core-shell structure, including a core of lithium magnesium silicate / carbon and a shell of metal fluoride fast ion conductor.
6. The application of the composite material as described in claim 5 as a negative electrode active material for batteries.
7. An application of the composite material as described in claim 5, characterized in that, It is used as a negative electrode active material, wherein the negative electrode active material is Li x Mg y Si z O n / C@MgF 2, The negative electrode active material is made of Li x Mg y Si z O n A core-shell structure with MgF2 as the core and MgF2 as the shell. The negative electrode active material Li x Mg y Si z O n The carbon in / C@MgF2 is a composite structure with carbon interpenetrating in pre-lithiated and pre-magnesized silicon suboxide.
8. A negative electrode, characterized in that, The negative electrode includes: Current collector; and The negative electrode material layer is located on the current collector. The negative electrode material layer includes the composite material as described in claim 5.
9. A lithium secondary battery, characterized in that, The lithium secondary battery includes: positive electrode; The negative electrode according to claim 8; and An electrolyte is located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Modified silica negative electrode material precursor and preparation method thereof
CN114524436A
Silicon negative electrode material with porous coating layer and preparation method thereof
CN114695847A